The Effects of Suburethral Tension Adjustable Sling (Remeex system) for Female Urinary Incontinence between Pure Intrinsic Sphincter Deficiency and Intrinsic Sphincter Deficiency with Overactive Bladder: Initial Experience with Propensity Score Matching - Sang Wook Lee; Woong Bin Kim; Kwang Woo Lee; Jun Mo Kim; Jae Heon Kim; Ji Eun Moon; Si Hyun Kim; Jae Joon Park; Young Ho Kim (Clinical and Experimental Obstetrics & Gynecology, 2022)
Objective: To compare the therapeutic efficacy after suburethral adjustable sling (Remeex system) for female stress urinary incontinence (SUI) between pure intrinsic s phincter deficiency (ISD) and ISD with overactive bladder (OAB) group. Methods: The study subjects were 86 female patients with ISD who underwent Remeex system to treat female SUI and who were available for 12 months follow-up. We retrospectively studied both patients who underwent Remeex system due to pure ISD (group I) and those who underwent Remeex system due to ISD with OAB (group II). Improvement in objective and subjective symptoms were retrospectively evaluated using a 1hr pad weight test, global response assessment (GRA) and overactive bladder symptom score (OABSS). Results: Group I included 43 patients and group II included 43 patients of mean ages 56.8 ± 7.5 and 57.4 ± 6.6 years, respectively. Use of 1 hr pad weight test showed that incontinence decreased after the procedures in both groups, and that of group I patients was significantly lower than that of group II patients. The mean GRA score was significant a higher score in group I. The OABSS of patients in group II were 8.2 ± 1.1 and 7.2 ± 1.1, respectively, before and at 12 months after operation, did differ significantly. The mean change of OABSS of group II patients was significantly more decreased than that of group I patients. Conclusions: The Remeex system showed a greater patient satisfaction and a higher cure rate in pure ISD than ISD with OAB in female patients with urinary incontinence.